Oil Palm Fibre and Nano-Silica Reinforced Epoxy Composite Material - Samuel, N.; Debnath, Sujan; Rahman, Muhammad; Nabinejad, O.; Moola, Mohan (Trans Tech Publications, Switzerland, 2014)
This paper presents a study on tensile properties of Nano Silicon Carbide (n-SiC) and oilpalm fibre (OPF) reinforced epoxy composites. The dosage of n-SiC and OPF are limited to 0%, 1%,3% & 5% by mass of the total epoxy material. As a part of the research, experimental study is carriedout on n-SiC and OPF based epoxy composites to investigate the tensile strength of the compositematerial. The utilization of 1% n-SiC& 1% treated OPF shows an improvement in tensile strengthcompared to the pure epoxy. The experimental results are also compared with 3-D finite elementanalysis results and a good agreement is observed between the experimental and the finite elementresults.